"Bajeng Dan Manusia Desa Pasir" Sebuah Buku Ilustrasi Cerita Tradisi Manusia Pasir Di Pulau Madura - Elfa Olivia Verdiana; Zainol Afif (Jurnal Desain Komunikasi Visual Asia, 2021)
One of Indonesia's cultural diversity is the Sand Man Tradition, namely the tradition of the people of East Legung Village, Batang Batang District, Sumenep Regency, East Java Province who sleep in the sand every day. This study aims to provide information effectively and attractively to the community about the Sand Man Tradition as a local culture. In addition, the purpose of this research is to provide awareness to the community of the importance of protecting and preserving the surrounding environment. This research is a descriptive study using a qualitative approach. The subjects of this research are the people of Madura Island, especially teenagers. Collecting data in this study using observation and interviews through questionnaires. The results showed that first, efforts to maintain tradition were carried out by utilizing visual media in the form of an interesting illustrated book so that information about the Tradition of Desa Pasir was conveyed well to the local community. Second, the effort to protect nature is not to throw away or not defecate into the sea or around the coast.